2018
DOI: 10.1080/02705060.2018.1431967
|View full text |Cite
|
Sign up to set email alerts
|

Serial discontinuity in naturally alternating forest and floodplain habitats of a Michigan (USA) stream based on physicochemistry, benthic metabolism, and organismal assemblages

Abstract: We tested the response of several different water quality metrics at 6 sites along a 4-km alternating forest (canopied) and floodplain (non-canopied) reach of the East Branch of the Black River, an undisturbed northern Lower Michigan trout stream, during summer 2015. Physicochemical parameters were unchanged between sites and reflected an undisturbed continuum. In-stream woody debris was higher at the forest sites, whereas relative canopy cover and sunlight intensity were higher at the floodplain sites. Both b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Specific conductance is a general indicator of nutrient, sediment, and organic matter concentrations ( Allan 2004 ). The values of HMC rivers were ~ 1/6 that of Michigan agricultural rivers ( Castillo et al 2000 ; Bernot et al 2006 ; Arango et al 2007 ; Houghton et al 2011 ) and ~1/3 that of other undisturbed Michigan rivers ( Houghton et al 2018 ), suggesting very low anthropogenic seston enrichment. Yanoviak and McCafferty (1996) found similar low specific conductance values when they sampled the Pine River, Mountain Stream, and the Salmon Trout River ~ 27 years ago.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Specific conductance is a general indicator of nutrient, sediment, and organic matter concentrations ( Allan 2004 ). The values of HMC rivers were ~ 1/6 that of Michigan agricultural rivers ( Castillo et al 2000 ; Bernot et al 2006 ; Arango et al 2007 ; Houghton et al 2011 ) and ~1/3 that of other undisturbed Michigan rivers ( Houghton et al 2018 ), suggesting very low anthropogenic seston enrichment. Yanoviak and McCafferty (1996) found similar low specific conductance values when they sampled the Pine River, Mountain Stream, and the Salmon Trout River ~ 27 years ago.…”
Section: Discussionmentioning
confidence: 91%
“…The high relative biomass of shredders (~ 50%) relative to scrapers (< 10%) in lakes of the Huron Mountains demonstrated the importance of coarse allochthonous input to lake food webs. While only caddisflies were sampled in this study, several other studies have demonstrated that trends in caddisfly FFG ecology usually reflect those of the overall insect assemblage ( Mackay and Wiggins 1979 ; Dohet 2002 ; Houghton et al 2011 ; Houghton et al 2018 ; Morse et al 2019a ; Houghton 2021).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Some challenges to using the immature stage, such as the difficulty of sampling all aquatic microhabitats representatively and identifying specimens to the species level, can be alleviated by using the winged adult stage, particularly that of taxonomically and ecologically diverse groups such as the caddisflies ( Trichoptera ) ( Gerth and Herily 2006 ; Chessman et al 2007 ; Cao and Hawkins 2011 ; Houghton et al 2011 ). Assemblages of caddisfly adults, particularly the relative abundance of specimens within different FFGs , have been shown in several studies to be indicative of stream conditions ( Dohet 2002 ; Houghton 2007 ; Blinn and Ruiter 2013 ; Houghton et al 2018 ). Such studies, however, treated all specimens equally and did not reflect the differences in biomass between different species.…”
Section: Introductionmentioning
confidence: 99%